Pengaruh Penghargaan dan Konsekuensi/Sanksi terhadap Motivasi Kerja Karyawan di Bank Xyz ABC Cabang Bandung - Martias, Daffa Dhiyaulhaq; Lahindah , Laura (Syntax Corporation, 2025)
This study aims to examine the influence of the reward and punishment system on employee work motivation at Bank XYZ, ABC Bandung Branch. The background of the research departs from the importance of a human resource management system in increasing employee productivity and loyalty. A quantitative approach was used using simple linear regression analysis. Data was collected through a questionnaire that was shared with 102 active employees of Bank XYZ. The results showed that the reward and punishment systems significantly affected employee motivation, with an adjusted R squared value of 0.827. Findings show that implementing performance-based rewards and applying fair and consistent sanctions can increase employees' enthusiasm, commitment, and responsibility in carrying out their duties. The study recommends that companies continue to strengthen their rewards and punishment strategies to create a productive, competitive, and conducive work environment.